Pre-electoral coalitions and post-election bargaining - Siddhartha Bandyopadhyay; Kalyan Chatterjee; Tomas Sjostrom (Rutgers University, Department of Economics, 2009)
Pre-electoral coalitions occur frequently in parliamentary democracies. They influence post election coalition formation and surplus division. We study a game theoretic model where political parties can form coalitions both before (ex ante) and after (ex post) the elections. Ex ante coalitions can commit to a seat-sharing arrangement, but neither to a policy nor to a division of rents from office; coalition members are even free to break up and join other coalitions after the election. Equilibrium ex ante coalitions are not necessarily made up of the most ideologically similar parties, and they form under (national list) proportional representation as well as plurality rule. They do not form just to avoid splitting the vote, but also because seat-sharing arrangements will influence the ex post bargaining and coalition formation. The ex post bargaining protocol matters greatly: there is more scope for coalition formation, both ex ante and ex post, under an Austen-Smith and Banks protocol than under random recognition.
Keywords: 330; Demokratie; Wahlkampf; Verhandlungen; Regierung; Politisches Ziel; Regierungskoalition; Theorie